PAROXYSMAL SUPRAVENTRICULAR TACHYCARDIA MANAGED WITH ACUPRESSURE OF NEI-GUAN (PC6): THE REPORT OF A CASE IN THE EMERGENCY DEPARTMENT - Chou, Pei-Chi; Chu, Heng-Yi (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: We described a 75-year-old man with a history of recurrent attacks of paroxysmal supraventricular tachycardia (PSVT). The patient presented to the emergency department (ED) with complaints of palpitations and chest tightness. Vagal stimulation maneuvers failed to convert the rhythmMaterials and Methods: Acupressure was applied on Nei-Guan (PC6). Results: Acupressure applied on PC6 immediately converted the tachycardia to a normal sinus rhythm, thus successfully terminated an episode of PSVT complicated with hypotension and chest pain in the patient reportedConclusion: Acupressure of PC6 is easy to perform and safe, and can be done when other resuscitative measures are ongoing the same time. It is harmless and appropriate for certain groups of patients such as the elderly, children and pregnant women and worth trying before the administration of medication.